Synthesis and Crystal Structure of Bis[2-((E)-(benzylimino)methyl)-6-bromo-4-chlorophenol]nickel(II) - Zhang, H.G. (Asian Journal of Chemistry, 2013)
A new nickel(II) complex, NiL2 with the Schiff base ligand HL = 2-((E)-(benzylimino)methyl)-6-bromo-4-chlorophenol, has been synthesized and characterized on the basis of elemental analyses and single crystal X-ray diffraction. The complex crystallizes in the monoclinic space group P2(1)/c with the cell parameters a = 10.6405(8) Å , b = 6.01904(3) Å, c = 20.5986 (18) Å, b = 102.3620(10)º, V = 1288.65(17) Å3, Z = 2, Dc = 1.819 g/cm3, μ (MoKa) = 7.024 mm-1, F(000) = 700, S = 1.036, the final R = 0.0590 and wR = 0.1368 for 2269 unique reflections (Rint = 0.0428) with 5879 observed ones (I > 2s(I)). The central nickel(II) is four coordinate and bonds to two nitrogen atoms and two oxygen atoms from two Schiff base ligands and the geometry around nickel(II) is a fairly square planar. The packing figure shows that there are no obvious interactions in the units of the complex.